Using aerial images to estimate production in forage cactus cultivars (Acta Scientiarum. Agronomy, 2025)
Predicting forage palm yield is a valuable tool for producers, aiding in harvest planning and crop management. This study aimed to evaluate the efficiency of using aerial images from a low-cost setup to estimate cladode production in four forage cactus cultivars. The experiment followed a randomized block design in a 4 x 4 factorial arrangement, with four replications. The first factor included the four cultivars: Giant, Miúda, Elephant Ear, and IPA Sertânia. The second factor involved four cladode harvest management strategies: (1) harvest at nine months, preserving the mother cladode; (2) harvest at nine months, preserving the mother and primary cladode; (3) harvest at 15 months, preserving the mother and primary cladode; and (4) harvest at 21 months, preserving the mother cladode. Before each harvest, aerial images were captured for each plot. The number of cladodes, fresh matter, and dry matter yield per harvest were calculated. Image processing was performed using the ExpImage package in the R software. The efficiency of predicting cactus yield using aerial images obtained with low-cost equipment was confirmed. Individually adjusted models for each cultivar provided greater precision in estimates. However, a single model for all four cultivars achieved a coefficient of determination greater than 77% for estimating fresh matter yield.